Synergistic Effect of Cinnamon Oil and Butyric Acid onGrowth Performance, Oxidative Stress, Immunological andIntestinal Histomorphology of Broiler Chickens - Doneria, Raina; Dubey, Meenu; Gendley, Manoj Kumar; Pathak, Rupal; Nety, Shraddha; Parmar, Mehtab Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present experiment evaluated the effect of cinnamon oil (CEO) and butyric acid (BA) on the performance, oxidative stress parameters, immune response and intestinal histomorphology of broiler chickens. Day-old broiler chicks (n=150) were distributed randomly into five experimental groups. The experimental groups were control: T0 (basal diet without bacitracin), T1 (basal diet + bacitracin @ 50 mg/ kg diet), T2 (basal diet + 400 mg/kg CEO), T3 (basal diet + 0.4 % BA), T4 (basal diet + 400 mg/kg CEO + 0.4% BA). Our results revealed that feed intake was significantly lower in T4, though a significant escalation in overall weight gain, and feed conversion ratio (FCR) was observed. Furthermore, T4 group exhibited a significantly higher defeathered, eviscerated, dressed weight and increased glutathione concentration as compared to T0. The haemagglutination inhibition (HI) titer against Newcastle Disease Virus (NCDV) was significantly higher in all the treatment groups as compared to T0. Additionally, significantly (p<0.05) improved villi height of duodenum and jejunum were observed in T4 group as compared to other groups. Conclusively, combining CEO and BA complemented the positive effects of each other and might be suitable substitutes to antibiotics for enhanced performance, immunity and antibiotic residue free meat production in poultry.